Exploring temperature and humidity environment combined with air quality index, black carbon, the short-term effect of combined exposure on respiratory disease mortality in Southwest China - Hengyu Su; Di Wu; Song Chen; Kaiyang Guo; Huifang Xie (PLoS ONE, 2025)
This study investigates the correlation, impact, and hysteresis effect of joint exposure to the Temperature-Humidity Index (THI), Air Quality Index (AQI), and Black Carbon (BC) on respiratory disease mortality (RDM) in urban areas of the southwest basin of China, characterized by a subtropical monsoon climate. Dose-response analysis of THI, AQI, BC using a non-restrictive cubic spline model, a time series analysis was conducted to assess the relative risk (RR) of death from respiratory diseases using the distributed lag nonlinear model (DLNM) and the generalized additive model (GAM) based on the quasi-Poisson distribution. The RCS curve of THI exhibits a ‘U’ shape, with THI=67 representing the lowest point of mortality risk. The RCS curves for BC and AQI are linear and demonstrate a positive correlation with mortality outcomes. The peak mortality risk associated with the AQI typically occurs at Lag 2-3, with T3A3 (THI ≥ 75 and AQI ≥ P90) contributing to the highest excess mortality [excess increased risk rate (ER) = 0.55, 95% CI: 0.20, 0.81]. The peak risk of mortality associated with BC occurs at Lag0, with the highest excess mortality resulting from T3B3 (THI ≥ 75 and BC ≥ P90) combined events (ER=0.28, 95% CI: 0.10, 0.58). The cumulative relative risk (CRR) was highest in T3, with the peak CRR of 3.99 (95% CI: 1.26, 7.11) observed in definition T3A3. The relative risk of interaction (RERI) reveals varying degrees of positive additive interactions (RERI > 0) among AQI, BC, and THI.